General aviation aircraft design : applied methods and procedures - Gudmundsson, Snorri (Butterworth-Heinemann, 2014)
Find the right answer the first time with this useful handbook of preliminary aircraft design. Written by an engineer with close to 20 years of design experience, General Aviation Aircraft Design: Applied Methods and Procedures provides the practicing engineer with a versatile handbook that serves as the first source for finding answers to realistic aircraft design questions. The book is structured in an ""equation/derivation/solved example"" format for easy access to content. Readers will find it a valuable guide to topics such as sizing of horizontal and vertical tails to minimize drag, siz.
Keywords: Airplanes -- Design and construction.; elektronické knihy; electronic books